1993
DOI: 10.1007/bf00310198
|View full text |Cite
|
Sign up to set email alerts
|

Total and regional bone mineral content in women treated with GnRH agonists

Abstract: Changes in bone mineral content induced by GnRH agonists were investigated by measuring total body bone mineral content (TBBM) and regional bone mineral content (BMC) (arms, legs, trunk, pelvis) and densities with dual energy X-ray absorptiometry in 25 premenopausal women before and after a 6-month treatment with gonadotropin-releasing hormone (GnRH) agonists. Biological markers of bone remodeling, estrogens, luteinizing hormone, and follicle-stimulating hormone were also measured. Weight and body mass index i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…However, its effects differ from what is observed during lactation (TABLE 3). Six months of acute estradiol deficiency causes 2-4% reductions in BMD of the spine with no losses at cortical sites (288,415,640,657,684,696,758,762,781,891,942). This is accompanied by increased serum calcium and phosphorus (265,288,640,657,781), increased fractional excretion of calcium (265,288,640,657,781,891,942), and low PTH and calcitriol (265,657,781).…”
Section: Human Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, its effects differ from what is observed during lactation (TABLE 3). Six months of acute estradiol deficiency causes 2-4% reductions in BMD of the spine with no losses at cortical sites (288,415,640,657,684,696,758,762,781,891,942). This is accompanied by increased serum calcium and phosphorus (265,288,640,657,781), increased fractional excretion of calcium (265,288,640,657,781,891,942), and low PTH and calcitriol (265,657,781).…”
Section: Human Datamentioning
confidence: 99%
“…Estradiol suppresses bone formation and resorption when administered as replacement therapy in peri-and postmenopausal women (305,750); it is not a potent stimulator of bone formation. Moreover, when reproductive-age women experience temporary estradiol deficiency induced by GnRH analog treatment, they lose a small amount of BMD and (unlike after lactation) most do not restore it afterwards (288,415,640,657,684,696,758,762,781,891,942). Earlier resumption of menses has correlated with an earlier apparent increase in bone mass after lactation (484,764), which suggests a benefit of higher estradiol.…”
Section: Human Datamentioning
confidence: 99%
“…Therefore, all the TRAP measured in this study was osteoclast-dependent. Although other biological markers of bone resorption are currently in fashion [3,22], TRAP meets more than enough criteria for considering it an adequate marker of bone resorption: 1) It correlates significantly and inversely with estrogen levels before and after Gn-RH agonist treatment [23], and in normal circumstances TRAP decreases with menarche and increases after menopause [24], 2) TRAP is elevated in diseases that are accompanied by a high remodeling rate [25], 3) TRAP correlates negatively with bone mass [23] and positively with alkaline phosphatase [26], as confirmed by this and other studies [23,26], 4) TRAP is sensitive to the effect of drugs that slow remodeling and reduce osteoclastic activity [27], 5) Osteoclastic TRAP is similar to serum TRAP 5b, as shown by electrophoretic mobility on acid gel [28], 6) Its specificity, because circulating TRAP 5b is exclusively osteoclastic in origin, increases its value as a marker of bone remodeling, 7) Finally, its determination in blood is easy [7] and free from the potential errors of markers quantitated in urine. Therefore, we do not think that more expensive markers, which require more complicated and sophisticated techniques, are necessary for evaluating bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Sowers et al [19] demonstrated a loss of bone mass density (BMD), comparing baseline values with those at 6 months postpartum; however the values of BMD returned to baseline levels at 12 months after parturition. GnRH agonists cause a preferential loss of bone mineral content in trunk osseous structures [20]. The maternal calcium losses through breast milk are considerable [12].…”
Section: Discussionmentioning
confidence: 99%